Community Integration and Pro-Environmental Behavior: Evidence from Household Waste Sorting Pilot in Nanjing, China - Li, Yajie (International Journal of Social Sciences and Public Administration, 2025)
Understanding the determinants of household waste sorting is crucial for improving urban environmental governance. While previous research has emphasized individual attitudes and infrastructural provisions, this study investigates the role of community integration-a multidimensional construct encompassing identity, participation, and support-in shaping sorting behavior. Drawing on survey data from 176 residents across 17 communities in Nanjing, China, and supplemented by 15 semi-structured interviews, we employ regression and mediation analysis to examine the psychological pathways linking community integration to waste sorting practices. Results show that stronger community integration significantly increases sorting frequency and accuracy, with trust, environmental responsibility, and self-efficacy mediating this relationship. These findings underscore the importance of community cohesion in bridging the intention–behavior gap and call for policy interventions that institutionalize community-based approaches to environmental behavior change.